2020
DOI: 10.3390/ijerph17217900
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Resistance Training on Blood Pressure in Preadolescents and Adolescents: A Systematic Review and Meta-Analysis

Abstract: The aim was to systematically review and meta-analyze the current evidence for the effects of resistance training (RT) on blood pressure (BP) as the main outcome and body mass index (BMI) in children and adolescents. Two authors systematically searched the PubMed, SPORTDiscus, Web of Science Core Collection and EMBASE electronic databases. Inclusion criteria were: (1) children and adolescents (aged 8 to 18 years); (2) intervention studies including RT and (3) outcome measures of BP and BMI. The selected studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…Aunque existen revisiones previas que han examinado el papel del EF en la aptitud física y su influencia en la presión arterial en niños y adolescentes (Lesinski et al, 2020;Guillem et al, 2020), ninguna ha abordado específicamente la influencia del EF en el perfil lipídico de esta población con sobrepeso y obesidad. Además, una revisión reciente demostró mejoras en varios parámetros de salud después de un programa de EF en adolescentes obesos, como la fuerza muscular, la capacidad cardiorrespiratoria y el IMC (Ribeiro et al, 2022), pero igualmente no evaluó parámetros relacionados con el perfil lipídico de los jóvenes.…”
Section: Resultsunclassified
“…Aunque existen revisiones previas que han examinado el papel del EF en la aptitud física y su influencia en la presión arterial en niños y adolescentes (Lesinski et al, 2020;Guillem et al, 2020), ninguna ha abordado específicamente la influencia del EF en el perfil lipídico de esta población con sobrepeso y obesidad. Además, una revisión reciente demostró mejoras en varios parámetros de salud después de un programa de EF en adolescentes obesos, como la fuerza muscular, la capacidad cardiorrespiratoria y el IMC (Ribeiro et al, 2022), pero igualmente no evaluó parámetros relacionados con el perfil lipídico de los jóvenes.…”
Section: Resultsunclassified
“…Although the positive effects of resistance training on BP values was registered in adults there is limited understanding about the static loading on BP in children and adolescents. The recently published meta-analysis of Guillem et al (18) did not clearly confirm the positive effect of static exercise in young people on BP, but a non-significant decrease in both, systolic and dyastolic BP was observed. Authors explained that although there is limited research in this topic, the results of their research suggest that "resistance training does not have an adverse effect on the BP of children and adolescents and may be beneficial in lowering BP and improving BMI in this population."…”
Section: Physiology Of Blood Pressure Changes During Exercisementioning
confidence: 88%
“…Supporting this, Carter et al found that a weight training program helped in reducing the systolic and diastolic BP in normotensive young adults [ 8 ]. In contrast, a meta-analysis found that weight training does not significantly change blood pressure in preadolescents and adolescents [ 9 ]. de Souza Nery et al reported that systolic blood pressure is not increased in normotensive but is slightly elevated among hypertensive individuals during rest after weight training sessions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%